Digital Storybook and Young Learners’ Reading Behavioral Engagement: A Systematic Review - Kadek Dian Nitami; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (English Education Department STKIP Agama Hindu Singaraja, 2026)
Reading behavioral engagement is an important aspect of students’ reading development, as it is reflected in observable behaviour such as attention, persistence, rereading, on task reading, and active interaction with the text. However, many young learners still struggle to maintain focus and active participation during reading activities, especially when using traditional reading material that rely heavily on text rather than visuals. Digital storybooks have emerged as an alternative reading material due to the integration of multimedia features that may support students’ engagement. This study employed a Systematic Literature Review (SLR) using the PRISMA framework to examine empirical studies published between 2020 and 2025 that investigated factors influencing young learners’ reading behavioral engagement through digital storybooks. Fourteen relevant articles were selected based on inclusion and exclusion criteria. The findings indicate that digital storybooks can effectively enhance students’ reading behavioral engagement when the multimedia features, such as narration, illustrations, and interactivity are well designed and aligned with pedagogical goals. Behavioral engagement is further strengthened through culturally relevant content, structured reading activities and teacher guidance. In contrast, excessive integrated multimedia may distract learners and reduce engagement. These findings provide a clearer framework for understanding how multimedia features influence young learners reading behavioral engagement. Overall, the study highlights the importance of thoughtful multimedia design and instructional support in digital reading contexts.